Preparation and investigation of hydrolyzed polyacrylonitrile as a preliminary biomedical hydrogel. Issue 1 (December 2015) - Park, Ji; Tai, Guo; Lee, Bo; Park, Seung; Jang, Ja; Lee, Jung; Kim, Jae; Park, Kwideok; Jang, Ju; Kim, Moon
Abstract Background Hydrolyzed polyacrylonitrile (HPAN) has attracted much attention as a hydrogel for a broad range of biomedical applications. Therefore, in this study, we prepared HPAN derivatives with controllable compositions by the radical polymerization of acrylonitrile (AN), methacrylic acid (MAA) andN -isopropylacrylamide (NIPAM) monomers. Results The prepared poly(AN-co-MAA-co-NIPAM) copolymers had different ratios of AN, MAA, and NIPAM and molecular weights ranging from 2000 to 50, 000. The copolymers were prepared as films to examine their properties. The prepared copolymer films showed different solubilities, contact angles, and swelling ratios. The properties of the copolymer films were affected by the hydrophobic PAN segments and the hydrophilic PMAA or PNIPAM segments. Conclusion Thus, we conclude that introducing PMAA and PNIPAM segments with different ratios and lengths into PAN segments could represent a method of controlling the hydrogel properties of copolymers.